Enhanced Charge‐ Discharge Behaviour of MnFe2O4 laden Composite Cathode for Lithium‐Sulfur Batteries. Issue 30 (16th August 2021) - Mathew, Deepa Elizabeth; Rani, G. Jenita; Jenis, D. Ponraj; Thomas, Sabu; Stephan, A. Manuel
Abstract: The Li−S battery commercialization has been hampered owing to challenging problems such as poor conductivity of elemental sulfur, volume change upon cycling, and shuttling of lithium polysulfide between the electrodes. To conquer these issues, a sensible electrode structure design is crucial. The incorporation of carbonaceous materials and metal oxides has been identified as an effective tool to foster the electrochemical properties of Li−S batteries. In this work, to confine polysulfide shuttling and to improve the conductivity of sulfur, MnFe2 O4 ‐seated rGO‐sulfur composite was prepared and used as a cathode. The lithium‐sulfur cell with MnFe2 O4 ‐seated rGO‐sulfur composite cathode showed outstanding electrochemical performance delivering a discharge capacity of 1300 mAh g −1 at 0.1 C‐rate on its first cycle and a stable cycling was attained at 0.5 C‐rate. In the composite cathode, each component functions for a specific reason: the rGO in the composite improves the conductivity of sulfur, while added‐ MnFe2 O4 not only confines polysulfides appreciably but also provides integrity to the cathode as evidenced by SEM analysis. The self‐discharge studies showed that the Li−S cell with MnFe2 O4 was capable of retaining its charge even after 90 h which has overhead the earlier reports. The Li−S system with MnFe2 O4 ‐laden cathode material exhibited better electrochemical properties than the un‐laden one. Abstract : Schematic illustration of polysulfide confinement by rGO‐ MnFe2 O4 particles. The added‐ MnFe2 O4 nanoparticles in the cathode material provided stability to the cathode, improved the initial discharge capacity and increased the cycling stability of the Li‐ S cell. The effective confinement of polysulfides by rGO‐ MnFe2 O4 particles is due to the electrostatic attraction between the added MnFe2 O4 particles and lithium polysulfides.